A Remote-Sensing Image Encryption Scheme Using DNA Bases Probability and Two-Dimensional Logistic Map - Hui Liu; Bo Zhao; Linquan Huang (IEEE Access, 2019)
Remote-sensing images contain lots of visual information about transportation systems, geomorphic conditions, and communal facilities. The secure storage and transmission of remote-sensing images are of great significance. This paper proposes a novel image encryption scheme-based DNA bases probability and applies it to remote-sensing images for data protection. First, the plain-image is randomly encoded in DNA rules and its result participates in DNA addition with DNA mask generated by 2-D logistic map. Second, the cryptosystem executes 2-D logistic map again with DNA bases probability against differential attacks. Third, the pixel-level rearrangement and the DNA base-level rearrangement are, respectively, implemented in order of chaos sequences for permutation and diffusion. The cipher-image has a uniform distribution, low coefficients, and ideal entropy. The cryptosystem has acceptable encryption speed ($speed=0.651308Mbit/s$ ) and high sensitivity to the plain-image and the security key. The experimental results show that the proposed algorithm can resist various existing attack schemes against remote-sensing images.